Electronic transport across hydrogen bonds in organic electronics. (2nd February 2015) - Meidanshahi, Reza Vatan; Mazinani, Shobeir K.S.; Mujica, Vladimiro; Tarakeshwar, Pilarisetty
Hydrogen bonds (H–bonds) are relatively weak and result from non–covalent interactions. Despite their relatively low strength compared to other bonds of biochemical relevance, they play a vital role in determining the structure and function of biological molecules owing to their directionality and cooperativeness. This has led to an intense effort in harnessing the properties of these hydrogen bonds in developing organic electronic devices. Though a large number of theoretical investigations have devoted their attention to the structural and energetic characteristics of hydrogen bonds, there are relatively few studies on the electronic transport characteristics of hydrogen bonds. In this work we evaluate the electrical conductance of a few model systems exhibiting the biologically important hydrogen bonds (N–H · · · O, O–H · · · O and N–H · · · N). We find that the calculated conductance can be correlated to the magnitude of the polarisabilities of the atoms involved in the formation of the hydrogen bonds. The implications of the current work in understanding electron transfer in biological systems is highlighted. We also address the utility of our work in the design and development of novel sensors and electronic devices based on the formation of weak hydrogen bonds.